KOMUNIKASI POLITIK DALAM PEMILIHAN KEPALA DAERAH DI SUMATERA UTARA - HENDRA KURNIA PULUNGAN (BAHAS, 2012)
The change of the provision in the 2004 constitution Number 32 and the effective of the 2008 constitution number 12 in which assert that the contestants of the Head District and Mayoral election (PEMILUKADA -Walikota) can also come from personal supported by a number of people. This fact indicates that the freedom of politics happen in the numerious members of society. The situation of democracy in the local level is obviously seen clearly in the contest of the head district and mayoral election. In the event of such election, either the head district or the mayor have been as an object to be run after. Whereas society is put as a primary subject.